Numerical simulations and case studies using Visual C++.Net - Salleh Shaharuddin, 1956- (Hoboken, N.J. : John Wiley, 2005)
Master the numerical simulation process required to design, test and support mobile and parallel computing systems. An accompanying ftp site contains all the Visual C++ based programs discussed in the text to help readers create their own programs.
Developing applications using Visual C++.Net -- Interfaces for numerical problems -- Matrix operations using Wizard -- Differential equation problems -- Drawing curves -- Working with images -- Visualizing a graph -- Graph applications -- Multiprocessor scheduling problem -- Discrete-event simulation -- Modeling wireless networks.
Includes bibliographical references.
Print version record.
Keywords: Microsoft Visual C; C (Computer program language); Computer simulation; Microsoft .NET Framework; Electronic books